Characteristic Study of Biodiesel from Used Cooking Oil using Nipah Skin Ash as a Heterogeneous Catalyst - Zainuddin Ginting; Rizka Mulyawan; Meriatna Meriatna; Tata Tirani; Asnadia Asnadia; Luthfi Mughni Anisa Haryono (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
One type of renewable alternative energy that has great potential to be developed is biodiesel. Biodiesel is a fuel consisting of a mixture of mono-alkyl esters of long-chain fatty acids made from renewable sources such as vegetable oils or animal fats. Such as vegetable oils or animal fats. One of the vegetable oil products that can be used as feedstock for biodiesel production is used cooking oil. Used cooking oil is used oil. The purpose of this research is to study the characteristics of the effect of catalyst mass, the ratio of used cooking oil mole to methanol mole, and the effect of adding THF 1:1 co-solvent on the purity of biodiesel using heterogeneous catalyst ash derived from Nipah fruit skin calcined at 500°C for 4 hours. The process variables were transesterification reaction time 60, 90, 120, and 150 minutes, a mole ratio of methanol to oil 1:19, 1:21, and 1:23 with the addition of THF: methanol v/v 1:1 co-solvent. Biodiesel properties such as density, viscosity, moisture content, and acid number were evaluated and compared with the Indonesian National Standard (SNI). The characteristics of biodiesel were obtained with a density of 860.2 Kg/m3 and a viscosity of 2.37 mm2/s. They contained 44.14% Palmitic acid and 43.04% Octadecenoic acid (oleic), following the Indonesian National Standard (SNI). The maximum yield obtained was 93.3598% using a mole ratio of oil: methanol 1:23 at 60°C for 120 minutes, TFT 1:1, and 3% catalyst mass. The results obtained in this study indicate that heterogeneous catalysts made from kapok skin can be used to produce biodiesel. Adding TFT co-solvent can increase biodiesel production and methyl ester yield so that high purity is obtained.